Is there a conflict between principles-based standard setting and structured electronic reporting with XBRL? - Dirk Beerbaum; Maciej Piechocki; Christoph Weber (European Financial and Accounting Journal, 2017)
National standard setters and external accounting observers continue to express concerns over a principles-based developed IFRS taxonomy. Considering the anticipated but unexpected SEC decision on March 3rd 2017 to adopt the IFRS taxonomy for electronic filings for Foreign Private Issuers by 2018 and the announcement of ESMA on December 22nd 2016 to base electronic filings in Europe on the IFRS taxonomy by 2020 signal that national regulators, external accounting observers and international regulators have a dissent. This paper reflects the expressed concerns by national standard setters. Applying a scientific ap-proach, a comprehensive literature review is performed. The research question is if the rules-based IFRS taxonomy implies a conceptual conflict with the principles-based IFRS. This paper concludes considering the academic literature although there is conceptual conflict between a principles-based accounting standard and the template-based taxonomy, from a normative perspective the IFRS taxonomy improves comparability and transparency supporting true and fair view. Our study also contributes to the principles-based vs. rule-based debate in the academic literature. The new aspect is the role of IT with structured electronic reporting, which requires detailed and specific requirements, for which rule-based accounting has advantages over principles-based accounting.
Keywords: M42; 650; IFRS taxonomy; Principles-based; XBRL